2005
DOI: 10.1387/ijdb.051974lb
|View full text |Cite
|
Sign up to set email alerts
|

Two members of the Fxr gene family, Fmr1 and Fxr1, are differentially expressed in Xenopus tropicalis

Abstract: The Fxr gene family is composed of three members, FMR1, FXR1 and FXR2. The FMR1 gene is involved in the fragile X syndrome, whereas for the other two members, no human disorder has been identified yet. An appropriate animal model to study in vivo gene function is essential to unravel the cellular function of the gene products FMRP, FXR1P and FXR2P, respectively. In Xenopus tropicalis both Fmr1 and Fxr1 were identified; however, unexpectedly Fxr2 was not. Here we describe the characterization of both Fmrp and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…One explanation for the relative weakness of FMRP's NLS might be that it requires additional factors to be activated. Perhaps cell-type or cell-cycle-specific proteins facilitate the nuclear import of FMRP under specific conditions, as in the early stages of Xenopus and zebrafish development when FMRP is primarily nuclear (9,81). In contrast, the removal of FMRP's NLS led to an improperly functioning protein that could not be evaluated for its ability to traffic in cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One explanation for the relative weakness of FMRP's NLS might be that it requires additional factors to be activated. Perhaps cell-type or cell-cycle-specific proteins facilitate the nuclear import of FMRP under specific conditions, as in the early stages of Xenopus and zebrafish development when FMRP is primarily nuclear (9,81). In contrast, the removal of FMRP's NLS led to an improperly functioning protein that could not be evaluated for its ability to traffic in cells.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether endogenous Xenopus FMRP is also present on LBCs, we stained nuclear spreads of uninjected oocytes with an antibody directed against Xenopus FMRP (9). Figure 10B and D show that anti-FMRP labeled the chromosomal loops, strongly suggesting that endogenous FMRP associates with nascent transcripts.…”
Section: Vol 29 2009 Fmrp Binds Mrnas In the Nucleus 221mentioning
confidence: 99%
See 1 more Smart Citation
“…However, several reports implicated a potential role for FMRP in the nucleus. Studies in Xenopus and zebrafish showed that at 2–3 hours post-fertilization, Fmrp is predominantly nuclear (Blonden et al, 2005; Kim et al, 2009; van’t Padje et al, 2005). In addition, Fmrp was found to decorate lampbrush chromosomes in Xenopus oocytes (Kim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As Fmr1 exon 12 is alternatively spliced Eichler et al, 1993;, its inclusion in Fmr1 transcripts leads to an in-frame extension of the variable loop of FMRP KH-2 domain. Interestingly, the segment encoded by Fmr1 exons 11 and 12 is absent in Fmr1 invertebrate orthologs and in the vertebrate paralogous genes, Fragile X-related 1 (FXR1) and 2 (FXR2) genes, potentially implicating FMRP in differential, specialized roles, as yet unknown (Wan et al, 2000;Tucker et al, 2004;Blonden et al, 2005).…”
Section: A Fmrp No Envelhecimento Cerebralmentioning
confidence: 99%